Implementasi Virtual Reality Pada Museum De Javasche Berbasis Android - Moch Bagus Setiawan; Mochammad Suryawinata (Forum Kerjasama Pendidikan Tinggi, 2021)
The museum is a place to see and study the history of how the history of civilization of a nation. The De Javasche Bank Museum was once the De Javasche Bank office until it was changed to the Bank Indonesia branch office in Surabaya. The progress of technology that is increasingly developing, coupled with the declining interest of the community especially students of the museum, making the museum to add technology in it with the aim of increasing public appeal. This is done to support the government's campaign so that the meme is a tourist and educational destination, so we need an interesting media introduction. This is because not everyone is familiar with the De Javasche Bank Museum. Virtual Reality (VR) is an example of technology where users can interact with a computer simulated environment. By applying VR to 3D applications on Android phones, people can become more familiar with De Javasche Bank Museum because the application works that displays 3D objects simulated in the form of virtual tours where users will tour the De Javasche Bank Museum. This can be a media for introducing the De Javasche Bank Museum which is more attractive to the public because of the 20 respondents, 17 respondents rated the application as interesting and informative.